Growth of Tin Oxide Thin Film by Aluminum and Fluorine Doping Using Spin Coating Sol-Gel Techniques - Susilawati Susilawati; Aris Doyan; Lalu Muliyadi; Syamsul Hakim (Jurnal Penelitian Pendidikan IPA, 2020)
Abstract: The growth of tin oxide thin film by Aluminum doping and Fluorine has been carried out with the sol-gel spin coating technique. The growth aims to determine the quality of the thin layer formed based on variations in doping aluminum and fluorine. The basic ingredients used were SnCl2.2H2O, while the doping materials used were Al (Aluminium) and F (Fluorine) with variations in dopant concentrations (0, 5, 10, 15, 20 and 25)%. The growth of a thin layer using measured glass (10x10x 3) mm as a substrate. The growth of thin films includes substrate preparation, sol-gel making, thin film making, and heating processes. The growth of thin layer was dripped on a glass substrate with sol-gel spin coating technique at 1 M sol concentration and treated with maturation for 24 hours. The next step is making a thin layer using a spin coater at a speed of 2000 rpm for 3 minutes. After that, the substrate is heated in an oven at 100°C for 60 minutes. The results showed that the transparency level of the tin oxide layer increases with increasing amounts of doping Aluminum and fluorine. Key words: Aluminum, Fluorine, Sol-gel, Spin Coating, Thin Film, Tin Oxide